Early‐life epileptic encephalopathy secondary to SZT2 pathogenic recessive variants. Issue 2 (June 2016) - Venkatesan, Charu; Angle, Brad; Millichap, John J.
Abstract: Advances in genetic testing have led to the identification of increasing numbers of novel gene mutations that underlie infantile‐onset epileptic encephalopathies. Recently, a mutagenesis screen identified a novel gene, SZT2, with no known protein function that has been linked to epileptogenesis in mice. Thus far, two clinical reports have identified children with different recessive mutations in SZT2 and varying clinical phenotypes. One case report described patients with epileptic encephalopathy and the other noted patients with cognitive deficiencies, but normal MRI and no epilepsy. This case report identifies novel mutations (a compound heterozygous frameshift and a nonsense variant) in the SZT2 gene with distinct clinical and radiographic findings relative to those previously reported. Our patient presented with intractable epilepsy at 2 months of age. Seizures were refractory to numerous antiepileptic medications and the patient finally achieved seizure cessation at age 3 years with a combination of divalproex and lamotrigine. Our patient had similar facial dysmorphisms (macrocephaly, high forehead, and down‐slanted palpebral fissures) to a previous case with truncating mutation. While developmental delay and cognitive deficiencies were present, our case had unique MRI findings suggesting migrational abnormalities not previously reported in other cases.